Laser processing for bevel termination of high voltage pn junction in SiC. (April 2016) - Kubiak, A; Ruta, Ł; Rosowski, A; French, P
Abstract: Proper edge termination of the p-n junction in silicon carbide is a key requirement in the fabrication of discrete devices able to withstand high voltages in reverse polarization. Due to the hardness of SiC the creation of the bevel termination remains difficult using mechanical machining. The use of laser beam sources with medium wavelength (532 nm) gives new possibilities in the machining of the silicon carbide. The paper presents the fabrication of the bevel termination structure in SiC using a green DPSS laser equipped with scanner and dedicated rotating sample holder. Characterization of the resulting structures proves the high potential of the proposed approach.